2008
DOI: 10.22495/cocv5i2c1p7
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of corporate governance information disclosure by Canadian banks

Abstract: The study reports on the disclosure of governance information by Canadian banks. The information was found through their corporate Web sites. The online information was taken from the Corporate governance Web page and through the annual reports and the proxy circulars. We focused on the disclosure of the corporate governance practices implemented by our sample of 8 banks. A coding sheet was developed to evaluate the corporate governance disclosure of our sample. Our analysis indicates that the bigger the bank,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…The first step that was taken was reviewing the extant literature on corporate governance disclosure research. A particular research paper was of immense significance (Maingot & Zeghal, 2008). A number of their suggested essential elements of disclosure have been adapted and integrated into the coding sheet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step that was taken was reviewing the extant literature on corporate governance disclosure research. A particular research paper was of immense significance (Maingot & Zeghal, 2008). A number of their suggested essential elements of disclosure have been adapted and integrated into the coding sheet.…”
Section: Methodsmentioning
confidence: 99%
“…From the onset, the intention of this research was to select some of the best banks in Africa to examine their corporate governance disclosure practices, as larger banks are known to have better disclosure practices than smaller banks, because corporate governance disclosure tends to generate considerable costs to firms (Maingot & Zeghal, 2008). More importantly, the research intends to examine the current state of corporate governance disclosure practices in Nigerian and South African banks so as to understand and inform on the nature, focus, and extent of corporate governance disclosure in the Nigerian and South African banking industries.…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…A study done by Maingot and Zeghal (2008) reported about the disclosure of governance information by the 'Canadian' banks. The authors focused on the disclosure of the CG practices implemented by eight banks.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…The purpose of the disclosure is to communicate and disseminate information about the firm's performance and governance to outside investors (Patel, & Dallas, 2002;Maingot & Zeghal, 2008). This information is not only called for by investors and shareholders to assess the performance of their investments but also by other critical stakeholders who are particularly concerned about the social and environmental policies.…”
Section: Corporate Governance Disclosurementioning
confidence: 99%